Epigenetic regulation by BAF (mSWI/SNF) chromatin remodeling complexes is indispensable for embryonic development. Issue 10 (18th May 2016) - Nguyen, Huong; Sokpor, Godwin; Pham, Linh; Rosenbusch, Joachim; Stoykova, Anastassia; Staiger, Jochen F.; Tuoc, Tran
ABSTRACT: The multi-subunit chromatin-remodeling SWI/SNF (known as BAF for Brg/Brm-associated factor) complexes play essential roles in development. Studies have shown that the loss of individual BAF subunits often affects local chromatin structure and specific transcriptional programs. However, we do not fully understand how BAF complexes function in development because no animal mutant had been engineered to lack entire multi-subunit BAF complexes. Importantly, we recently reported that double conditional knock-out ( dcKO ) of the BAF155 and BAF170 core subunits in mice abolished the presence of the other BAF subunits in the developing cortex. The generated dcKO mutant provides a novel and powerful tool for investigating how entire BAF complexes affect cortical development. Using this model, we found that BAF complexes globally control the key heterochromatin marks, H3K27me2 and -3, by directly modulating the enzymatic activity of the H3K27 demethylases, Utx and Jmjd3. Here, we present further insights into how the scaffolding ability of the BAF155 and BAF170 core subunits maintains the stability of BAF complexes in the forebrain and throughout the embryo during development. Furthermore, we show that the loss of BAF complexes in the above-described model up-regulates H3K27me3 and impairs forebrain development and embryogenesis. These findings improve our understanding of epigenetic mechanisms and their modulation by the chromatin-remodeling SWI/SNF complexes that control embryonic development.